Injuries in elite football: should sports medicine perform better? - Eirale, C.; Bisciotti, G. (The Journal of Sports Medicine and Physical Fitness, 2021)
A recent article by Ekstrand et al. showed that injury rates decreased in men`s professional footballl. Injury incidence dropped progressively 3% per season for both training injuries (95% CI : 1-4%, P=0.002) and match injuries (95% CI : 2-3%, P<0.001) during the 18-year study period.1 This seems to be confirmed by clinical trials showing the effectiveness of prevention programs, like the FIFA 11+, in football.2 At a first glance, we could therefore speculate that sport medicine has improved providing these comforting results especially considering that the game has become faster and more intense. However, analyzing the article more carefully, it is shown that only injury (and reinjury) incidence decreased while burden and severity did not. But what does this mean? It means that we have less injuries, but we do not treat them faster, therefore the total impact on players` absence is unchanged. Prevention is the tool to reduce injury incidence. Therefore, possibly, effective programs of prevention have been implemented in professional football. This is certainly good news, meaning that clinicians, performance and technical staff are becoming more and more aware of the effectiveness of this tool and are cooperating to implement it to reduce injury incidence.